Antibody-mediated depletion of select leukocyte subsets in blood and tissue of nonhuman primates - Sutton, Matthew S.; Bucsan, Allison N.; Lehman, Chelsea C.; Kamath, Megha; Pokkali, Supriya; Magnani, Diogo M.; Seder, Robert; Darrah, Patricia A.; Roederer, Mario (Frontiers in Immunology, 2024)
Understanding the immunological control of pathogens requires a detailed evaluation of the mechanistic contributions of individual cell types within the immune system. While knockout mouse models that lack certain cell types have been used to help define the role of those cells, the biological and physiological characteristics of mice do not necessarily recapitulate that of a human. To overcome some of these differences, studies often look towards nonhuman primates (NHPs) due to their close phylogenetic relationship to humans.To evaluate the immunological role of select cell types, the NHP model provides distinct advantages since NHP more closely mirror the disease manifestations and immunological characteristics of humans. However, many of the experimental manipulations routinely used in mice (e.g., gene knock-out) cannot be used with the NHP model. As an alternative, the in vivo infusion of monoclonal antibodies that target surface proteins on specific cells to either functionally inhibit or deplete cells can be a useful tool. Such depleting antibodies have been used in NHP studies to address immunological mechanisms of action. In these studies, the extent of depletion has generally been reported for blood, but not thoroughly assessed in tissues.Here, we evaluated four depleting regimens that primarily target T cells in NHP: anti-CD4, anti-CD8, anti-CD8, and immunotoxin-conjugated anti-CD3. We evaluated these treatments in healthy unvaccinated and IV BCG-vaccinated NHP to measure the extent that vaccine-elicited T cells which may be activated, increased in number, or resident in specific tissuesare depleted compared to resting populations in unvaccinated NHPs. We report quantitative measurements of in vivo depletion at multiple tissue sites providing insight into the range of cell types depleted by a given mAb. While we found substantial depletion of target cell types in blood and tissue of many animals, residual cells remained, often residing within tissue. Notably, we find that animal-to-animal variation is substantial and consequently studies that use these reagents should be powered accordingly.